Evaluasi Implementasi Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) Jenis Sludge oil pada Industri Pengolahan Minyak Bumi Berdasarkan Regulasi Lingkungan - Hadarianto Dio Febrianto Nainggolan; Tastaptyani Kurnia Nufutomo; Thariq Miswary (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The implementation of hazardous and toxic waste (B3) management in the petroleum refining industry requires a systematic approach to control potential environmental risks from waste generation to its utilization or transfer to licensed waste management facilities. One type of hazardous waste requiring special management is Sludge oil, a residue generated from tank cleaning and storage tank maintenance activities that contains hydrocarbons and other hazardous compounds. This study aimed to evaluate the implementation of Sludge oil hazardous waste management at PT X based on Government Regulation No. 22 of 2021 and the Regulation of the Minister of Environment and Forestry No. 6 of 2021. A descriptive qualitative approach was employed through field observations, interviews with personnel involved in waste management, document reviews, and implementation evaluation at each stage of the waste management process. The evaluation covered waste identification and characterization, packaging, temporary storage, transportation, transfer to licensed third parties, and waste utilization. The results showed that the Sludge oil management system was implemented sequentially in accordance with the company's operational procedures, beginning with waste characterization based on oil content to determine the appropriate management method, followed by temporary storage in jumbo bags at the hazardous waste temporary storage facility, transportation by licensed transporters, and utilization by authorized third parties as alternative fuel and alternative material. During the period of July–December 2025, a total of 2,806.81 tons of Sludge oil waste was generated, of which 2,762.61 tons were transferred to licensed waste management facilities, while the remaining waste was temporarily stored in accordance with the company's operational procedures. The evaluation indicated that the implementation of Sludge oil waste management complied with the technical and administrative requirements stipulated in the applicable environmental regulations. These findings provide an overview of the implementation of a structured Sludge oil waste management system in the petroleum refining industry.